A Methods engineering study on Chrome Dazzler Enterprises - Ang, Angela Bianca L.; Ching, Dioselle S.; Pato, Maria Carmela C.; Tongco, Serafin Benedicto U. II. (Diliman, Quezon City College of Engineering, 2002)
Chrome Dazzler Enterprises was established in 1962 and started as a small shop offering electroplating especially chrome plating and powder coating services for different products. Some of its major customers are hotels, establishments, appliance and consumer product companies, motor shops, automotive ehtusiasts and hobbyists or the automotive and motorcycle industry as a whole. This methods engineering study was conducted to determine and address problems encountered by the company to more efficiently serve their customers. It focuses on the causes of bottleneck situations in the stripping and pre-plating quality control sections of Chrome Dazzler Enterprises. It aims to identify the reasons for the said setbacks, to worl on any possible solutions, to evaluate, and to improve the system. Addressing these problems and causes would translate into a decrease in the total time on chrome-plating different products. Decrease in cycle and standard times, and hence delay, results in a higher labor productivity, which implies that they could carry out more activities and entertain more clients; thus, increasing their profitability. The groupd started evaluating the chrome-plating process from the stripping, polishing, pre-plating quality control, racking, and plating sections of the plant. The group documented the whole process including different aspects of the plant such as the facility layout, machinery and equipment, as well as manpower services. Using the different analytical tools learned in the course, the group applied the Ishikawa diagram, the root causes and core problems were identified. The core problems to be assessed are that the pre-plating quality control section lacks manpower and there is a difficulty in job order scheduling. Then the group used work measurement techniques; specifically work sampling, in generating alternatives. The alternatives generated by the group are to either hire new workers for the preplating quality control section or to just re-assign workers from other sections in the plant. For the job order scheduling problem, the standard times for each process and each type of product was recorded and from these times, a schedule was made to minimize the delays and maximize the outputs they can accomplish for the day.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis